Thermoplastics for Network Applications
Thermoplastic resins composed of polyamide and additives address the challenges of limited range and structural integrity in millimeter-wave 5G communication networks by providing both mechanical strength and low transmission loss, effectively supporting millimeter-wave signal transmission.
Patent Information
- Application Number
- JP2022554912
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-02-26
- Filing Date
- 2021-03-12
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-03-12
AI Technical Summary
Existing materials used in antenna concealment assemblies for millimeter-wave 5G communication networks face challenges such as limited range, obstruction by physical obstacles, and the need for materials with both high structural integrity and low transmission loss.
The development of thermoplastic resins comprising polyamide, such as nylon-6,6, combined with additives like glass fibers, UV resistant additives, and flame retardants, which provide mechanical strength, toughness, and improved durability while maintaining low transmission loss for millimeter-wave frequencies.
These thermoplastic resins offer enhanced mechanical properties and reduced moisture absorption, allowing for effective signal transmission and structural integrity, even in challenging environmental conditions.
Smart Images

Figure 0007657237000023 
Figure 0007657237000024 
Figure 0007657237000025
Abstract
Description
[Technical field]
[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority to U.S. Provisional Application No. 62 / 989,105, filed March 13, 2020, U.S. Provisional Application No. 63 / 142,081, filed January 27, 2021, and U.S. Provisional Application No. 63 / 154,035, filed February 26, 2021, which are incorporated by reference herein.
[0002] FIELD OF THEINVENTION The present disclosure relates to thermoplastic resins in millimeter wave network applications suitable for 5G (abbreviated for fifth generation of mobile device communications) related technologies. The disclosed resins can be used to make enclosures or housings for electronic components capable of receiving or transmitting electromagnetic signals in the high frequency radio and microwave regimes. [Background technology]
[0003] Advances in global communications technology are driving faster, more reliable and more affordable products and services. Technologies such as 4G LTE and 5G are evolving to meet the needs of a global consumer base.
[0004] In recent years, 5G wireless communication technologies in particular have been advancing at a much faster pace. 5G coverage can be separated into two regimes in the electromagnetic spectrum: i) millimeter wave (mmWave), and ii) low / mid band. mmWave technology uses frequencies in the range of 6-100 GHz, e.g., above 24-25 GHz, e.g., in the range of 28-39 GHz, while low / mid band uses frequencies below 6 GHz.
[0005] One of the hurdles for mmWave 5G communications networks is that they require newer and more numerous transmitters to function properly, which limits their range significantly compared to low-band and mid-band networks. Also, mmWave 5G networks have issues passing through physical obstacles such as buildings and structures, which limits the transmission range of one, which is undesirable for consumers to adopt this technology.
[0006] Materials used in antenna concealment assemblies are generally customized structures including fiberglass, fiberglass reinforced plastic ("FRP"), polyurethane foam, ABS plastic, other composite materials, or both. These materials provide a reasonable degree of structural integrity and strength, as well as a reasonable degree of radio frequency (RF) transparency for low frequency cellular applications. However, such customized structures and material selections are less viable for higher spectrum broadband and satellite applications due to the extreme RF transparency requirements when implemented on a widespread scale.
[0007] Approaches to developing low transmission loss materials included Hitachi Chemical's low dielectric constant material AS-400HS, which Hitachi reported improved electrical properties and processability compared to polytetrafluoroethylene (PTFE) and aromatic liquid crystal polymers (LCP), an example of which can be found in New Low Transmission Loss Material for Millimeter-wave Radar Module "AS-400HS", Hitachi Chemical Technical Report No. 58., Tanigawa et al. Additional approaches to developing low transmission loss materials included low density foam housings and panels such as those used in RayCap INVISIWAVE™ products.
[0008] At the same time, there remains a need to provide materials that have suitable high transmission for millimeter wave applications while providing structurally useful tensile strength, as well as toughness and improved durability. Summary of the Invention
[0009] The present disclosure relates to a thermoplastic resin comprising a polyamide and at least one of a second polyamide or an additive.
[0010] The polyamide may include nylon-6, nylon-6,6, mixtures thereof, or copolymers thereof. The polyamide may further include nylon-6, nylon-6.6, copolymers thereof that include at least one repeat unit of poly(hexamethylene terephthalamide), poly(hexamethylene isophthalamide), or a copolymer of poly(hexamethylene terephthalamide) and poly(hexamethylene isophthalamide), mixtures thereof, copolymers thereof, or combinations thereof.
[0011] The additives may be selected from the group consisting of reinforcing fibers, UV resistant additives, flame retardant additives, antistatic additives, impact modifiers, colorants, water repellents, and mixtures thereof.
[0012] The present disclosure also relates to articles formed from the thermoplastic resins of the present disclosure, such as, for example, housings or parts of housings for telecommunications devices (such as RF transmitter / receiver antennas, circuitry, or combinations thereof).
[0013] There are many advantages and unexpected properties associated with the disclosed subject matter. For example, according to various embodiments, panels including nylon-6,6 can provide good mechanical strength while providing adequate transmission properties, especially when glass fibers are included in the nylon-6,6. This is unexpected due to the hygroscopic nature of nylon-6,6. It would be thought that the hygroscopic nature of nylon-6,6 would allow too much moisture uptake, which would destroy the transmission properties. However, the inventors have surprisingly found that this is not the case. [Brief description of the drawings]
[0014] The drawings illustrate generally, by way of example, but not by way of limitation, various aspects of the present invention. [Figure 1] 1 is a graph showing moisture gain data for 1.5 mm thick test sample plaques measured by ISO 1110 procedure, according to various examples of the present disclosure. [Diagram 2] 1 is a graph showing moisture gain data for 3.0 mm thick test sample plaques measured by ISO 1110 procedure, according to various examples of the present disclosure. [Figure 3A] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for dry as molded (DAM) (or dry) samples at two frequencies according to various examples of the present disclosure. [Figure 4A] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for dry as molded (DAM) (or dry) samples at two frequencies according to various examples of the present disclosure. [Figure 5A] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for dry as molded (DAM) (or dry) samples at two frequencies according to various examples of the present disclosure. [Figure 6A]1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for dry as molded (DAM) (or dry) samples at two frequencies according to various examples of the present disclosure. [Figure 7A] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for dry as molded (DAM) (or dry) samples at two frequencies according to various examples of the present disclosure. [Figure 8A] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for dry as molded (DAM) (or dry) samples at two frequencies according to various examples of the present disclosure. [Figure 9A] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for dry as molded (DAM) (or dry) samples at two frequencies according to various examples of the present disclosure. [Figure 10A] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for dry as molded (DAM) (or dry) samples at two frequencies according to various examples of the present disclosure. [Figure 11A] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for dry as molded (DAM) (or dry) samples at two frequencies according to various examples of the present disclosure. [Figure 12A] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for dry as molded (DAM) (or dry) samples at two frequencies according to various examples of the present disclosure. [Figure 13A]1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for dry as molded (DAM) (or dry) samples at two frequencies according to various examples of the present disclosure. [Figure 14A] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for dry as molded (DAM) (or dry) samples at two frequencies according to various examples of the present disclosure. [Figure 15A] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for dry as molded (DAM) (or dry) samples at two frequencies according to various examples of the present disclosure. [Figure 16A] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for dry as molded (DAM) (or dry) samples at two frequencies according to various examples of the present disclosure. [Figure 3B] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for conditioned (or wet) samples at two frequencies according to various examples of the present disclosure. [Figure 4B] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for conditioned (or wet) samples at two frequencies according to various examples of the present disclosure. [Figure 5B] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for conditioned (or wet) samples at two frequencies according to various examples of the present disclosure. [Figure 6B] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for conditioned (or wet) samples at two frequencies according to various examples of the present disclosure. [Figure 7B] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for conditioned (or wet) samples at two frequencies according to various examples of the present disclosure. [Figure 8B] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for conditioned (or wet) samples at two frequencies according to various examples of the present disclosure. [Figure 9B] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for conditioned (or wet) samples at two frequencies according to various examples of the present disclosure. [Figure 10B] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for conditioned (or wet) samples at two frequencies according to various examples of the present disclosure. [Figure 11B] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for conditioned (or wet) samples at two frequencies according to various examples of the present disclosure. [Figure 12B] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for conditioned (or wet) samples at two frequencies according to various examples of the present disclosure. [Figure 13B] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for conditioned (or wet) samples at two frequencies according to various examples of the present disclosure. [Figure 14B] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for conditioned (or wet) samples at two frequencies according to various examples of the present disclosure. [Figure 15B]1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for conditioned (or wet) samples at two frequencies according to various examples of the present disclosure. [Figure 16B] 1 is a graph showing transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of thickness (mm on the X-axis) for conditioned (or wet) samples at two frequencies according to various examples of the present disclosure. [Figure 17A] 13 depicts a cyclone plot showing insertion loss (dB) data according to Example 18 of the present disclosure. [Figure 17B] 13 depicts a cyclone plot showing insertion loss (dB) data according to Example 18 of the present disclosure. [Figure 18A] 1 illustrates array antenna data measured at three azimuth angles: 0°, 30°, and 60°, according to one embodiment of the present disclosure. [Figure 18B] 1 illustrates array antenna data measured at three azimuth angles: 0°, 30°, and 60°, according to one embodiment of the present disclosure. [Figure 19] 1 is a perspective view of a low transmission loss panel according to various examples of the present disclosure. [Figure 20] 1A to 1C are schematic diagrams of various panels or housings including a window according to Comparative Example 1 of the present disclosure. [Figure 21] 26A-C are schematic diagrams of various panel windowless panels or housings according to a twenty-sixth embodiment of the present disclosure. [Figure 22] 1 illustrates a cyclone plot showing insertion loss (dB) data according to one embodiment of the present disclosure. [Figure 23A] 25 illustrates array antenna data measured at three azimuth angles, 0°, 30°, and 60°, in accordance with Example 24 of the present disclosure. [Figure 23B] 25 illustrates array antenna data measured at three azimuth angles, 0°, 30°, and 60°, in accordance with Example 24 of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] definition Reference will now be made in detail to certain aspects of the disclosed subject matter, examples of which are illustrated in part in the accompanying drawings. While the disclosed subject matter will be described in conjunction with the enumerated claims, it will be understood that the illustrated subject matter is not intended to limit the claims to the disclosed subject matter.
[0016] It should be understood that throughout this document, values expressed in range format should be interpreted in a flexible manner to include not only the numerical values expressly recited as the limits of the range, but also all individual numerical values or subranges subsumed within the range, as if each numerical value and subrange were expressly recited. For example, a range of "about 0.1% to about 5%" or "about 0.1% to 5%" should be interpreted to include not only about 0.1% to about 5%, but also individual values (e.g., 1%, 2%, 3%, and 4%) and subranges (e.g., 0.1% to 0.5%, 1.1% to 2.2%, 3.3% to 4.4%) within the stated range. A statement of "about X to Y" has the same meaning as "about X to about Y" unless otherwise indicated. Similarly, a statement of "about X, Y, or about Z" has the same meaning as "about X, about Y, or about Z" unless otherwise indicated.
[0017] In this document, the terms "a," "an," or "the" are used to include one or more unless the context clearly dictates otherwise. The term "or" is used to refer to a non-exclusive "or" unless otherwise indicated. The statement "at least one of A and B" has the same meaning as "A, B, or A and B." In addition, any terms or terminology used herein and not otherwise defined should be understood to be for descriptive purposes only and not limiting. Any use of section headings is intended to aid in the reading of the document and should not be construed as limiting. Information associated with a section heading may occur within or outside that particular section.
[0018] In the methods described herein, unless a temporal or operational order is explicitly recited, acts may be performed in any order without departing from the principles of the present disclosure. Moreover, specified acts may be performed simultaneously unless express claim language dictates that they be performed separately. For example, an act recited in a claim to perform X and an act recited in a claim to perform Y may be performed simultaneously in a single operation, with the resulting process falling within the literal scope of the claimed process.
[0019] As used herein, the terms "about" or "substantially" can allow for a degree of variation, for example, within 20%, within 15%, within 10%, within 5%, or within 1% of a stated value or the limits of a stated range, and includes the exact stated value or range.
[0020] As used herein, the term "polyamide" refers to a polymer having repeating units linked by amide bonds. Polyamides can be derived from monomers containing aliphatic, semi-aromatic, or aromatic groups. Polyamides include nylons, such as nylon 6,6 or nylon 6, and can refer to polyamides derived from a single monomer, two different monomers, or three or more different monomers. Thus, the term polyamide includes dimonomer polyamides. Polyamides can be nylons having dicarboxylic acid and diamine monomer units as monomer units. For example, if the dicarboxylic acid monomer unit is adipic acid and the diamine is hexamethylenediamine, the resulting polyamide can be nylon 6,6. Nylon 6 is a polyamide with caprolactam monomers. Polyamides can be copolymers that can be prepared from aqueous solutions or blends of aqueous solutions containing more than two monomers. In various aspects, polyamides can be produced by polymerization of dicarboxylic acid and diamine monomers. In some cases, polyamides can also be produced via polymerization of amino carboxylic acids, amino nitriles, or lactams. Suitable polyamides include, but are not limited to, those polymerized from the monomer units described herein. The term "polyamide" includes polyamides such as PA6, PA66, PA11, PA12, PA612, nylon-66 / 6T, etc. However, the term may be modified when expressly made to exclude a particular polyamide. For example, in some embodiments, the polyamide may be a polyamide other than PA11, PA12, and PA612, or the polyamide may be a polyamide other than nylon-66 / 6T.
[0021] As used herein, the terms "N6," "nylon-6," or "PA6" refer to a polymer synthesized by polycondensation of caprolactam. The polymer is also known as polyamide 6, nylon-6, and poly(caprolactam).
[0022] As used herein, the terms "N66," "nylon-6,6," or "PA66" refer to a polymer synthesized by the polycondensation of hexamethylenediamine (HMD) and adipic acid. The polymer is also known as polyamide 66, nylon-66, nylon-6-6, and nylon-6 / 6.
[0023] The polymers described herein can be terminated in any suitable manner. In some embodiments, the polymer can be terminated with an end group independently selected from a suitable polymerization initiator, -H, -OH, substituted or unsubstituted (C1-C20) hydrocarbyl (e.g., (C1-C10) alkyl or (C6-C20) allyl), interrupted by 0, 1, 2, or 3 groups independently selected from -O-, substituted or unsubstituted -NH-, and -S-, poly(substituted or unsubstituted (C1-C20) hydrocarbyloxy), and poly(substituted or unsubstituted (C1-C20) hydrocarbylamino).
[0024] In this disclosure, the term "DAM" or "dry" refers to a dry molded test specimen.
[0025] In this disclosure, the terms "wet" or "cond" or "conditioned" refer to a conditioned sample.
[0026] The term "substantially uniform attenuation" refers to a reduction in signal strength across a uniform thickness of a sample as the electromagnetic signal traverses the thickness of the sample in a direction perpendicular to the surface of the sample.
[0027] As used herein, the term "attenuation coefficient" refers to a calculated value for the measured wave attenuation (or loss) in decibels (dB) when a wave signal of a particular frequency (in GHz) passes through a medium of approximately a particular structural thickness (in cm). The unit of measurement for attenuation coefficient is dB / GHz.cm. By way of example, an attenuation coefficient value of 1.0 dB / GHz.cm means a wave loss of 1.0 dB per unit of GHz per cm of medium thickness. composition
[0028] The present disclosure relates to materials that exhibit low transmission loss for electromagnetic signals at frequencies associated with 5G networks.
[0029] The low transmission loss material can include at least one polyamide. The polyamide can be PA6 or a blend thereof, such as PA4,6, PA6,6, PA6,9, PA6,10, PA6,12, PA10,12, PA12,12, PA6, PA11, PA12, PA66 / 6T, PA6I / 6T, PADT / 6T, PA66 / 6I / 6T, or PA6 / PA66. In some examples, the polyamide can include 6I repeat units (hexamethylene isophthalamide), 6T repeat units (polyhexamethylene terephthalamide), or a combination of 6I / 6T repeat units. When a combination of 6I and 6T repeat units is present, the 6I and 6T repeat units can be present in any suitable weight ratio, such as about 96:4 to about 10:90 weight:weight of 6I:6T, about 80:20 to about 20:80 weight:weight, about 70:30 to about 30:70 weight:weight, or about 60:40 to about 40:60 weight:weight, or 6I:6T. In some examples, the polyamide can be PA66:DI, with a molar weight ratio between PA66 and DI in the range of 85:15 to 96:4 (weight:weight).
[0030] As used herein, "PA66 / DI" refers to a type of copolyamide of polyhexamethylene dipamide (nylon-6,6 or N66 or PA66) and "DI" (which is a combination of 2-methyl-pentamethylene diamine (or "MPMD") and isophthalic acid). MPMD is commercially available as INVISTA Dytek® A amine and known in the industry as "D" in the abbreviated formulation label. Isophthalic acid is commercially available and known in the industry as "I" in the abbreviated formulation label. The formulation "PA66 / DI" used in the examples of this disclosure had an RV of 45 and a composition of 92:8 PA66:DI (wt / wt), with the "DI" portion being about 40:60 D:I (wt / wt). Other non-limiting copolyamides suitable for use in place of the PA66 / DI used in the examples include 66 / D6, 66 / DT, 6T / DT, 66 / 610, or 66 / 612.
[0031] The polyamides can include nylon-6 (e.g., PA6) and nylon-6,6 (e.g., PA6,6). The polyamide can be nylon-6.6, and the composition can, optionally, be substantially free of all other polyamides (e.g., nylon-6.6 can be the only polyamide used to form the composition).
[0032] In some examples, the polyamide can be in the range of about 30% to about 100%, about 50% to about 95%, or less than, equal to, or greater than 30%, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 100% by weight of the housing. In some examples, the polyamide can comprise the majority of the housing material with a small amount of fibers (e.g., fiberglass, carbon fiber, basalt, aramid, polymer, silica, mineral fibers, or mixtures thereof), additives, or mixtures thereof. In some examples, the housings described herein are comprised of (polyamide and fibers. In some examples, the housings described herein are comprised of polyamide, fibers, and additives. In some examples, the housing can be comprised of nylon-6,6 and fibers. In some examples, the housing can be comprised of nylon-6,6, fiberglass, and additives. In some examples, the housing can be comprised of nylon-6,6.
[0033] Low transmission loss material is approximately 0.7 g / cm 3 ~Approx. 10g / cm 3 , about 0.7g / cm 3 ~about 5g / cm 3 , about 2g / cm 3 ~about 5g / cm 3 , about 0.75g / cm 3 ~ approx. 4g / cm 3 , 0.8g / cm 3 ~ approx. 4g / cm 3 , about 0.8g / cm 3 ~About 3g / cm 3 , about 0.85~about 3g / cm 3 , or about 0.7 g / cm 3,0.8,0.9,1.0,1.1,1.2,1.3,1.4,1.5,1.6,1.7,1.8,1.9,2.0,2.1,2.2,2.3,2.4,2.5,2.6,2.7,2.8,2.9,3.0,3.1,3.2,3.3,3.4,3.5,3.6,3.7,3.8,3.9,4.0,4.1,4.2,4.3,4.4,4.5,4.6,4.7,4.8,4.9,5.0,5.1,5.2,5.3,5.4,5 0.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, or about 10.0 g / cm 3 The density may be adjusted to lie in the above range.
[0034] Suitable polyamides according to the present disclosure have tensile modulus and tensile strength values sufficient to enable devices formed from the polyamide to withstand environmental stresses. By way of example, suitable polyamides include those having a tensile modulus in the range of 1,000 MPa to 50,000 MPa, e.g., 1,000 MPa to 40,000 MPa, e.g., 1,000 MPa to 30,000 MPa. By way of example, suitable polyamides include those having a tensile strength of less than, equal to, or greater than about 30, 50, 100, 150, 200, 250, 300, 350, or 400 MPa.
[0035] In some examples, PA66 with 20 wt% GF may have a tensile strength in the range of about 100 MPa to about 150 MPa at a temperature of 50° C. and in the range of about 70 MPa to about 100 MPa at a temperature of about 23° C. In some examples, PA66 with 30 wt% glass fiber may have a tensile strength in the range of about 140 MPa to about 190 MPa at a temperature of 50° C. and in the range of about 100 MPa to about 130 MPa at a temperature of about 23° C. In some examples, PA66 with 20 wt% glass fiber may have a tensile strength in the range of about 100 MPa to about 150 MPa at a temperature of 50° C. and in the range of about 70 MPa to about 100 MPa at a temperature of about 23° C. In some examples, PA66 with polyphenylene ether may have a tensile strength in the range of about 45 MPa to about 65 MPa at a temperature of 50° C. and in the range of about 40 MPa to about 55 MPa at a temperature of about 23° C. In some examples, PA66 with polyphenylene ether and 20% by weight glass fiber may have a tensile strength in the range of about 100 MPa to about 130 MPa at a temperature of 50°C, and in the range of about 80 MPa to about 100 MPa at a temperature of about 23°C.
[0036] Additionally, suitable polyamides have a Charpy impact strength of 30 KJ / m at 23°C without a notch. 2 ~Non-breaking, e.g., 40KJ / m 2 ~200KJ / m 2 , 40KJ / m 2 ~150KJ / m 2 , or 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, or 200KJ / m 2 In some examples, PA66 with 20% by weight glass fiber has a toughness of about 98 KJ / m at a temperature of 50° C. 2 ~About 110KJ / m 2 and at a temperature of about 23°C, it is about 53KJ / m 2 ~Approx. 72KJ / m 2 In some examples, PA66 with 30% glass fiber by weight can have an unnotched Charpy impact value of about 110 KJ / m at a temperature of 50° C.2 ~About 120KJ / m 2 and at a temperature of about 23°C, it is about 89 KJ / m 2 ~About 100KJ / m 2 In some examples, PA66 with polyphenylene ether can have an unnotched Charpy impact value in the range of about 240 KJ / m at a temperature of 50° C. 2 ~Approx. 340KJ / m 2 and at a temperature of about 23°C, it is about 310 KJ / m 2 ~Approx. 370KJ / m 2 In some examples, PA66 with polyphenylene ether and 20% by weight glass fiber can have an unnotched Charpy impact value of about 73 KJ / m at a temperature of 50° C. 2 ~Approx. 76KJ / m 2 and at a temperature of about 23°C, it is about 79 KJ / m 2 ~About 82KJ / m 2 In some examples, PA66 with 20% glass fiber by weight can have an unnotched Charpy impact value of about 10 KJ / m at a temperature of 50° C. 2 ~About 22KJ / m 2 and at a temperature of about 23°C, it is about 7KJ / m 2 ~about 8.5KJ / m 2 In some examples, PA66 with 30% glass fiber by weight can have a notched Charpy impact value of about 15 KJ / m at a temperature of 50° C. 2 ~About 27KJ / m 2 and at a temperature of about 23°C, it is about 11 KJ / m 2 ~About 14KJ / m 2 In some examples, PA66 with polyphenylene ether can have a notched Charpy impact value in the range of about 24 KJ / m at a temperature of 50° C. 2 ~About 35KJ / m 2 and at a temperature of about 23°C, it is about 20KJ / m 2 ~About 23KJ / m 2In some examples, PA66 with polyphenylene ether and 20% by weight glass fiber can have a notched Charpy impact value in the range of about 11 KJ / m at a temperature of 50° C. 2 ~About 14KJ / m 2 and at a temperature of about 23°C, it is about 11 KJ / m 2 ~About 12KJ / m 2 The steel sheet may have a Charpy notched impact value in the range of
[0037] The polyamide may be a neat polyamide. The polyamide may be a single polyamide. The polyamide may be a copolymer. The polyamide material may be a blend of polyamides. The polyamide material may include a blend of non-polyamide materials or compounds. Examples of such materials or compounds include additives and reinforcing fibers. Other examples of such materials or compounds include polyethers (such as polyphenylene ether (PPE)), polyolefins (polyethylene, polypropylene, polybutylene, acrylonitrile-butadiene-styrene (ABS) resins, polybutylene terephthalate (TBT), propylene carbonate (PC)), and blends thereof.
[0038] Reinforcement of the polyamide can be accomplished, for example, by incorporating glass fiber, carbon fiber, basalt, aramid, polymer, silica, or mineral fibers into the polyamide melt, for example, from an extruder. If present, the reinforcing fibers can range from less than, equal to, or greater than about 5% to about 50%, about 10% to about 30%, about 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50% by weight of the panel 100.
[0039] In addition to or instead of including reinforcing fibers, the polyamide material may further include at least one additive or additive package. When present, the at least one additive or additive package may range from about 0.1% to about 60% by weight, such as from about 0.5% to about 55% by weight, such as from about 0.75% to about 50% by weight, based on the total polyamide material. Examples of additives or additive packages include UV resistance additives, flame retardant additives, antistatic additives, impact modifiers (e.g., pigments), heat stabilizer additives, and water repellency additives. In some examples, an article including polyamide may include a flame retardant coating disposed on an exterior surface of the article.
[0040] Examples of suitable impact modifier additives may include maleated polyolefins. Examples of suitable maleated polyolefins include maleated polyolefins available under the trade name AMPLIFY GR (available from Dow Chemical Co, Midland MI, USA) (examples include Amplify GR 202, Amplify GR 208, Amplify GR 216, and Amplify GR 380); maleated polyolefins available under the trade name EXXELOR VA 1803, Exxelor VA 1840, Exxelor VA 1202, Exxelor PO 1020, and Exxelor PO 1015 available from ExxonMobil, Irving TX, USA; Examples include maleated polyolefins available under the trade name ENGAGE™ 8100 available from Eppendorf, MI, USA, and maleated polyolefins available under the trade name BONDYRAM® 7103 available from Ram-On Industries LP.
[0041] Examples of suitable flame retardants include, for example, organic phosphorus compounds, such as organic phosphates (including trialkyl phosphates (such as triethyl phosphate, tris(2-chloropropyl)phosphate, etc.), and triaryl phosphates (such as triphenyl phosphate, diphenyl cresyl phosphate, etc.), resorcinol bisdiphenyl phosphate, resorcinol diphosphate, aryl phosphates, etc.), phosphites (including trialkyl phosphites, triaryl phosphites, and mixed alkyl-aryl phosphites), phosphonates (including diethyl ethyl phosphonate, dimethyl methyl phosphonate), polyphosphonates (including melamine polyphosphonate, ammonium polyphosphonate), polyphosphites, polyphosphonates, phosphinates (including aluminum tris(diethyl phosphinate)), etc.); halogenated flame retardants (such as chlorendic acid derivatives and chlorinated paraffins); organic bromines (such as decabromodiphenyl ether, ether, decaBDE), decabromodiphenylethane, polymeric bromine compounds (brominated polystyrene, brominated carbonate oligomers (BCO), brominated epoxy oligomers (BEO), tetrabromophthalic anhydride, tetrabromobisphenol A A, TBBPA, and hexabromocyclododecane (HBCD); metal hydroxides (such as magnesium hydroxide, aluminum hydroxide, cobalt hydroxide, and hydrates of the aforementioned metal hydroxides); and combinations thereof. The flame retardant may be a reactive type flame retardant, including phosphorus-based, 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phospha-phenanthrene-10-oxide, phosphorus-containing lactone-modified polyester, ethylene glycol bis(diphenyl phosphate), neopentyl glycol bis(diphenyl phosphate), amine- and hydroxyl-functionalized siloxane oligomers. These flame retardants may be used alone or in combination with other flame retardants.
[0042] Examples of suitable UV additives include UV absorbers, quenchers, hindered amine light stabilizers (HALS), or mixtures thereof. UV absorbers are a type of light stabilizer that functions by competing with chromophores to absorb UV light. Absorbers convert harmful UV light into harmless infrared light or heat that is dissipated through the polymer matrix. Carbon black is an effective light absorber. Another UV absorber is rutile titanium dioxide, which is effective in the 300-400 nm range. Hydroxybenzophenones and hydroxyphenylbenzotriazoles are also suitable UV stabilizers with the advantage of being suitable for neutral or transparent applications. Hydroxyphenylbenzotriazoles are not very useful in thin sections less than 100 micrometers. Other UV absorbers include benzophenones for polyvinyl chloride, benzophenones for polycarbonate, and benzotriazoles and hydroxyphenyltriazines for polycarbonate. UV absorbers have the advantage of low cost, but may only be useful for short-term exposure. The quencher returns the excited state of the chromophore to the ground state by an energy transfer process. The energy transfer agent functions by quenching the excited state of the carbonyl group formed during the photooxidation of the polymeric material and through the decomposition of the hydroperoxide. This prevents bond scission and ultimately the formation of free radicals. Hindered amine light stabilizers are long-term heat stabilizers that act by scavenging the free radicals formed during the photooxidation of the polymeric material and thus limiting the photodegradation process. The ability of hindered amine light stabilizers to scavenge the radicals generated by UV absorption is explained by the formation of nitroxy radicals by a process known as the Denisov Cycle. Although there are wide structural differences in hindered amine light stabilizers, most share the 2,2,6,6-tetramethylpiperidine ring structure. Hindered amine light stabilizers are high-quality UV stabilizers for a wide range of polymeric materials.Hindered amine light stabilizers are also very effective in polyolefins, polyethylenes, and polyurethanes, but are not useful in polyvinyl chloride.Non-limiting examples of optional additives include adhesion promoters, biocides, antifog agents, antistatic agents, antioxidants, adhesives, blowing agents, catalysts, dispersants, extenders, smoke suppressants, impact modifiers, initiators, lubricants, nucleating agents, pigments, colorants and dyes, optical brighteners, plasticizers, processing aids, release agents, silanes, titanates and zirconates, slip agents, antiblocking agents, stabilizers, stearates, ultraviolet light absorbers, waxes, catalyst deactivators, and combinations thereof.
[0043] Non-limiting examples of optional additives include adhesion promoters, biocides, antifog agents, antistatic agents, antioxidants, adhesives, blowing agents, catalysts, dispersants, extenders, smoke suppressants, impact modifiers, initiators, lubricants, nucleating agents, pigments, colorants and dyes, optical brighteners, plasticizers, processing aids, release agents, silanes, titanates and zirconates, slip agents, antiblocking agents, stabilizers, stearates, ultraviolet light absorbers, waxes, catalyst deactivators, and combinations thereof. Articles made from the thermoplastic resins of the present disclosure
[0044] The thermoplastic resins presented in this disclosure have industrial utility in wireless network infrastructure. Thus, the present disclosure further relates to articles formed with the thermoplastic resins disclosed herein. Such compositions can be used in many areas, including communication devices, electronics, and power systems. Exemplary articles formed from thermoplastic resins include, but are not limited to, power cable terminations, miniaturized antennas, antenna concealment, cell phone casings, housings for electronic components, power converters / conditioners, optical fibers, fiber termination boxes, radios, diplexers / multiplexers, coaxial cables, and combinations thereof. The article can take the form of an enclosure for an electronic device or a portion of an enclosure for an electronic device. When the article is a portion of an enclosure, the article can be a panel.
[0045] FIG. 19 shows an example of a panel 100 according to the present disclosure. According to various embodiments, an enclosure can be formed from a plurality of joined panels 100. Alternatively, an enclosure can be formed by contoured panels 100, as further described below. The formed panel 100 can be characterized by its dielectric constant. For example, the dielectric constant of a panel 100 including polyamide can be in the range of less than, equal to, or greater than about 2.50 to about 4.00, about 2.75 to about 3, or about 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, or about 4.0 in the frequency range of 3 to 40 GHz. These values can be measured, for example, using Activity Standard Test Method (ASTM) D2520. The formed panel 100 can be further characterized by its dissipation factor (DF), which can be in the range of less than, equal to, or greater than about 0.004 to about 0.025, about 0.010 to about 0.020, or 0.004, 0.006, 0.007, 0.008, 0.009, 0.010, 0.011, 0.012, 0.013, 0.014, 0.015, 0.016, 0.017, 0.018, 0.019, 0.020, 0.021, 0.022, 0.023, or 0.024 in the frequency range of 3 to 40 GHz. These values can be measured, for example, using ASTM D2520. The attenuation of panel 100 may be 1 dB to 0 dB when the panel thickness is 0.5 mm to 6 mm for signals with frequencies between 500 MHz and 6 GHz, when the panel thickness is 0.5 mm to 4.5 mm for signals with frequencies between 24 GHz and 30 GHz, when the panel thickness is 0.5 mm to 4 mm for signals with frequencies between 36 GHz and 40 GHz, or when the panel thickness is 0.5 mm to 3.5 mm for signals with frequencies between 76 GHz and 81 GHz.
[0046] When the frequency is 500 MHz to 6 GHz, the signal impingement angle with the surface is 90±5°, the composition is selected from any of the thermoplastic resins in Table 1, the desired attenuation is 1 dB to 0 dB, then the suitable thickness may be 0.5 mm to 6 mm.
[0047] When the frequency is 24 GHz to 30 GHz, the signal impingement angle with the surface is 90±5°, the composition is selected from any of the thermoplastic resins in Table 1, the desired attenuation is 1 dB to 0 dB, then the suitable thickness may be 0.5 mm to 4.5 mm.
[0048] When the frequency is 36 GHz to 40 GHz, the signal impingement angle with the surface is 90±5°, the composition is selected from any of the thermoplastic resins in Table 1, the desired attenuation is 1 dB to 0 dB, then the suitable thickness may be 0.5 mm to 4 mm.
[0049] When the frequency is 76 GHz to 81 GHz, the signal impingement angle with the surface is 90±5°, the composition is selected from any of the thermoplastic resins in Table 1, the desired attenuation is 1 dB to 0 dB, then the suitable thickness may be 0.5 mm to 3.5 mm.
[0050] A panel 100 made substantially (e.g., to the extent that impurities made from other materials or negligible structural properties) from a transmission loss material can take many different forms. For example, the panel 100 can be configured to be a panel 100 for covering a transmission element such as an antenna. In some examples, the panel 100 can be a component of a molded article. The molded article can be, for example, a housing designed to cover an antenna or other transmission element. When present as a portion of a housing, the panel 100 can be the only portion of the molded article that includes a low transmission loss material. Forming the panel 100 as a portion of a housing can be useful to provide weatherproof shielding for electronic devices. Alternatively, in some aspects, the entire housing can be formed of the same material as the panel 100. As used herein, the term "weatherproof" refers to the ability of a housing to withstand reasonable exposure to the elements (e.g., sun, rain, wind, or a combination thereof) while substantially maintaining its structural integrity.
[0051] The panels can have any suitable dimensions. The panels can be from about 0.5 mm to about 6 mm, 1 mm to about 2 mm, or 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3. The thickness may be in the range of less than, equal to, or greater than 3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4, 4.1, 4.1, 4.2, 4.3, 4.5, 4.6, 4.7, 4.8, 4.9, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, or 6 mm. FIG. 19 is a perspective view of an example of a panel 100. The thickness of the panel 100 is defined between opposing major surfaces 102 and 103. Surfaces 102 and 103 of panel 100 may be, for example, circular (or substantially circular, allowing for some deviation from a perfect circle), or otherwise rounded or polygonal in shape. Examples of suitable polygons include triangular shapes (e.g., equilateral, right, obtuse, isosceles, or acute triangles), quadrilateral shapes (e.g., square or rectangle), pentagonal shapes, hexagonal shapes, heptagonal shapes, octagonal shapes, or any higher order polygonal shapes.
[0052] The opposing major surfaces 102 and 103 of the panel 100 can have a flat profile or a curved profile. A curved profile can include a single curve or a series of undulations. A curved profile can give the panel 100 a generally convex or concave shape. Each adjacent undulation can be evenly spaced relative to one another, or can be unevenly spaced relative to one another. Additionally, either of the opposing major surfaces 102 and 103 can include one or more protrusions, such as ribs. If present, the ribs can help increase the strength of the panel 100. Each surface can be substantially smooth or textured. The opposing major surfaces can have the same profile, or each major surface can have a different profile.
[0053] The panel 100 can be formed by any of several suitable processes, including injection molding, thermoforming, and compression molding. The disclosed panel 100 can be optionally formed in a single molding operation or in a multi-shot process (where the surrounding material is the same or different from that of the disclosed panel 100). Generally, a multi-shot process is performed with one machine programmed to perform two injections in one cycle. In the first cycle, a nozzle injects plastic into the mold. The mold is then automatically rotated and a different type of plastic is injected into the mold from a second nozzle. Dual injection molding optimizes the copolymerization of hard and soft materials to create strong molecular bonds. The result is a single part with production and feature advantages. It can be used for a variety of product designs across all industries. It also allows molding using clear plastics, colored graphics, and stylish finishes, improving product functionality and market value.
[0054] In applications where the panel 100 cannot be formed through injection molding, the panel 100 may be formed through extrusion. In some instances of extrusion, a die disposed at the end of an extruder may have a shape that is a negative impression of the intended shape of the panel 100. In yet some further instances, any portion of the panel 100 may be formed through an additive manufacturing process.
[0055] Electronic devices can be housed in enclosures prepared from the materials disclosed herein. Such enclosures can be either fixed installations such as poles, buildings, roofs, or mobile installations such as vehicles, aircraft, bicycles, boats, clothing, etc. The enclosures can be designed according to application standards in terms of volume, weight, ease of access for maintenance / repair, aesthetics (color, finish, appearance, etc.), or other criteria. The electronic devices can be, for example, AC or DC power supplies 5G mmWave and 4G radiators; AC / DC rectifiers or remote power supply units, fiber connectivity enclosures, radio frequency synthesizers or diplexers, warning and intrusion systems, AC and DC power distribution panels, 5G antennas, or 5G receivers.
[0056] The reinforcing fibers can serve to increase the tensile strength and toughness of the article. The amount of reinforcing fibers added can be sufficient to impart the desired tensile strength and toughness to the article while not compromising the low transmission loss characteristics of the material.
[0057] Material is 1g / cm 3 The ability to achieve density values above 100% can serve to increase the tensile strength and toughness of the resulting article, which is in direct contrast to articles that include, for example, foam materials.
[0058] The decision regarding the particular polyamide or blend of polyamides to use in an article may be a function of the tensile strength, toughness, or both of the respective polyamides.
[0059] The polyamide(s) that can be used in injection molding, extrusion, or additive manufacturing processes can be provided as individual pellets. The individual pellets can include polyamide or a mixture of polyamides with any of the additives described herein. The pellets can further include any of the reinforcing fibers described herein. In some examples, the diameter or length of the individual pellets can independently range from about 1 mm to about 5 mm, from about 2 mm to about 4 mm.
[0060] Alternatively, in some examples, the pellets may contain only polyamide or a mixture of polyamides. These pellets can then be heated to soften them, and any additives, reinforcing fibers, or both can be added to the softened pellets and mixed. After mixing, the mixture of polyamide, additives, reinforcing fibers, or subcombinations thereof can be subjected to an injection molding process, an extrusion process, or an additive manufacturing process. EXAMPLES
[0061] Various aspects of the present invention may be better understood with reference to the following examples, which are provided by way of illustration and are not intended to be limiting of the invention to the examples described herein.
[0062] Particular combinations of composition, surface profile, and structural thickness can surprisingly result in molded articles that exhibit useful dielectric constants and high transparency for millimeter waves. General procedure for generating compounded materials
[0063] A twin screw extruder with a minimum 18 mm diameter co-rotating screw with 40-56 L / D (e.g., L / D ratio of 40-56) was used for compounding. The unit has one main feeder and a minimum of three side feeders. A feed rate of at least 1 kg / hr was used. Twin screw co-rotating / swirl at a speed of at least 1000 RPM was sufficient to provide high shear for the compounding function. Total compounder throughput was at least 15 kg / hr.
[0064] The compounding unit had at least three vent ports, one atmospheric port, and two vacuum ports. The rotating twin screws imparted total body momentum to the heated mass inside the barrel, and the barrel was heated along its length in zones at temperatures ranging from 250 to 310 °C.
[0065] The processing section of the twin screw compounder was set up to suit the needs of various processes and to allow a wide variety of processes, including compounding processes. Polymer, fillers, and additives, as required, were continuously fed into the first barrel section of the twin screw using metered feeders. The product was transported along the screw and melted and mixed by kneading elements in the plasticizing section of the barrel. The polymer then traveled along a side port, where it was mixed with fillers or additives, as required, and fed into a degassing zone, from where it was fed into a pressure building zone, and then exited the die as a race through a hole of at least 3 mm. The cast race was fed into a water bath to cool it and allow it to be cut into chips through a pelletizer. The unit was designed to be able to withstand a die pressure of at least 70 bar. It could include a die with a minimum of four holes, each at least 3 mm in diameter for pelletizing.
[0066] Compounded pellets of polyamide having a diameter of 3 mm and a length of 3-5 mm were produced using the above equipment. The moisture content of the pelletized polyamide material was less than about 0.2% by weight. General steps for producing a molded panel
[0067] The injection molding machine used (Demag Sumitomo Sytec 100 / 200) contained a feed throat and a single rotating screw in a temperature zoned barrel, where the zones could range from 40-320°C for melting the nylon 6,6-based resin, and the screw traveled within the barrel to inject a quantity of molten resin into a mold, which was at a temperature of 60-90°C for the nylon 6,6-based resin. The mold resulted in solid parts or samples, including those suitable for testing such as flammability bars of the desired dimensions.
[0068] In these instances, flammability ratings were established by conducting tests that are functionally equivalent to the UL94 standard. Materials used in the examples
[0069] The feedstock PA6 neat polyamide used herein is commercially available as Ultramid® polyamide from BASF, as Akulon® polyamide from DSM Engineering Materials, or the like.
[0070] As used herein, feedstock PA66 neat polyamide is INVISTA nylon-66 (or N66) grade commercially available under the trade name INVISTA™ U4800 polyamide resin available from INVISTA, Wichita KS. PA66 has a nominal RV range of 42-50. Feedstock PA66 has a higher RV in the range of 80-240.
[0071] As used herein, "6I / 6T" is commercially available as EMS Grivory G21 from EMS-Chemie (North America) Inc. of Sumter, South Carolina, USA.
[0072] As used herein, the terms "PA66-6I / 6T" or "PA66+6I / 6T" refer to a blend of PA66 and 6I / 6T. For example, "PA66+6I / 6T(70+30)" is a 70:30 (wt:wt) nylon:6I / 6T blend of PA66 and 6I / T.
[0073] As used herein, "PA66-GF30" is glass fiber reinforced nylon 66. "GF30" indicates a glass fiber content of 30% by weight.
[0074] As used herein, "PA66-GF20" is glass fiber reinforced nylon 66. "GF20" indicates a glass fiber content of 20% by weight.
[0075] As used herein, "PA66-PPE" refers to a commercially available thermoplastic polymer blend of PA66 and polyphenylene ether (abbreviated as PPE). Such materials are available from Asahi Kasei, SABIC, Mitsubishi, and LG Chem, such as LG Chemical LUMILOY® TX5002 High Flow PPE / PA Alloy, Mitsubishi Lemalloy® C61HL PPE-PA66 Alloy, or the like. Suitable PA66-PPE blends may have a mass ratio range of 90:10 to 10:90, such as 80:20, 70:30, 60:40, 50:50, 40:60, 30:70, 20:80, etc.
[0076] As used herein, "PA66-PPE-GF20" is glass fiber reinforced nylon-66-PPE. "GF20" indicates a glass fiber content of 20% by weight.
[0077] As used herein, "PPE" refers to commercially available materials, such as those available from Asahi Kasei, SABIC, Mitsubishi, and LG Chem.
[0078] As used herein, "PA66-IM-GF30" is a nylon-66 containing impact modified polyolefin having 30% by weight GF.
[0079] Neat polycarbonate (PC) is a commercially available material such as that available from Lotte Chemical.
[0080] As used herein, "PA66 / DI" is known as a copolymer of hexamethylene adipamide and 2-methyl-1,5-pentamethylene-isophthalamide. The PA66 / DI used in the examples has a relative viscosity (RV) of 45 and contains about 92:8 (wt:wt) PA66:DI. The "DI" portion in PA66 / DI is about 50:50 (molar) or about 40:60 (wt:wt) D:I. Material samples tested:
[0081] Seven resin samples were tested in these examples. The seven resins are listed below in Table 1. The moisture content of the starting resin pellets was measured by an AquaTrac instrument prior to molding the plaques. [Table 1] Test methods used in the examples
[0082] ISO 1110: Accelerated conditioning of polyamide samples.
[0083] ASTM D2520 Standard Test Method for Complex Dielectric Constant (Dielectric Constant) of Solid Electrical Insulating Materials at Microwave Frequencies and Temperatures up to 1650°C (Method B, Resonant Cavity Perturbation Technique).
[0084] ASTM D789 Relative Viscosity (RV) Measurement Method.
[0085] UL94 standard flammability (V-0 / V-1 / V-2) rating determination method. Determination of moisture gain
[0086] Each resin sample was molded as a 100 x 134 x 3 mm plaque and a 100 x 155 x 1.5 mm plaque. The plaques were stored in foil bags in a dry molded state, so the moisture in the DAM plaques is expected to be the same in the pellets fed to the molding machine.
[0087] Starting from the dry-molded (DAM) condition, the plaques were conditioned using the ISO 1110 procedure.
[0088] The ISO 1110 standard provides a method for accelerated conditioning of polyamide samples, where the samples are kept in a humidity chamber with an atmosphere at 70°C with 62% relative humidity (RH). The samples are allowed to gain moisture until they reach equilibrium weight, which is determined by measuring the mass of the sample every day, and the conditioning end point is indicated by the sample reaching a constant mass. This procedure represents a very similar moisture gain as that obtained if the sample was kept in a 50% RH atmosphere at 23°C until it reached equilibrium moisture, which can be more than 9 months depending on the thickness of the sample.
[0089] For each of the seven samples, both 1.5 mm and 3 mm thick plaques were conditioned in a humidity chamber according to ISO 1110 procedures. For each test sample and plaque thickness, three replicates were weighed to track moisture gain. In all cases, the three replicates gave excellent agreement in weight gain.
[0090] Figure 1 (for 1.5 mm thick plaques) and Figure 2 (for 3.0 mm thick plaques) show the average weight gain (in weight % compared to the initial DAM weight) for each sample tested. Table 2 below lists the final equilibrium moisture levels of the seven samples tested. [Table 2] Dielectric constant and dissipation factor measurements:
[0091] Approximately ⅛ inch thick plaques of each material were used for dielectric constant and dissipation factor measurements using the guidelines of ASTM D2520, Method B. All plaques were approximately 3.9 inches by 5.3 inches by 0.12 inches.
[0092] Two replicates of each material (see FIG. 1) were prepared for testing at each required test frequency, as described below, including 3 GHz, 5 GHz, 10 GHz, 20 GHz, 30 GHz, and 40 GHz.
[0093] Table 3 lists the test sample size for each test frequency. All test samples were prepared such that the length of the test sample corresponded to the plaque flow direction. Two plaques of each material (AN in Table 1) were used to prepare the test samples. One replicate for each frequency was produced from each plaque. [Table 3]
[0094] All testing was performed at ambient laboratory conditions. Test conditions were performed at 24° C. and 46% RH. All samples were handled in a manner that limited exposure to ambient laboratory conditions during both sample preparation and testing. Dielectric constant measurement:
[0095] Testing was performed using the guidelines outlined in ASTM D2520 ("Standard Test Method for Complex Permittivity (Dielectric Constant) of Solid Electrical Insulating Materials at Microwave Frequencies and Temperatures up to 1650°C"). Method B (resonant cavity perturbation technique) was used. The electric field in the cavity was parallel to the length of the test sample. The measured dielectric constant data for all samples tested at six frequencies are listed in Table 4 below. The precision of the dielectric constant was approximately ±1% for the frequency range of 3 GHz to 20 GHz and approximately ±2% for the range of 30 GHz to 40 GHz. The results are shown in Table 4. [Table 4] Dissipation factor measurement:
[0096] Testing was performed using the guidelines outlined in ASTM D2520 ("Standard Test Method for Complex Permittivity (Dielectric Constant) of Solid Electrical Insulating Materials at Microwave Frequencies and Temperatures up to 1650°C"). Method B (resonant cavity perturbation technique) was used. The electric field in the cavity was parallel to the length of the test sample. The dissipation factor resolution was approximately ±5% for the three GHz-20 GHz frequency ranges and ±10% for the 30 GHz to 40 GHz range. The results are shown in Table 5. [Table 5] Waveform Modeling:
[0097] The above dielectric constant and dissipation factor measurement data (Tables 4 and 5) for the seven tested samples, DAMs, and conditions were used for waveform modeling. Various commercial code packages are available for such modeling, for example, from Altair Feko™, a comprehensive computational electromagnetics (CEM) code.
[0098] Waveform modeling was used to determine the transmission loss (in decibels, dB) as well as the reflection (dB) at each of the test frequencies (in GHz) for each of the seven test samples, each of which had varying thicknesses. Test Method
[0099] Mechanical testing included testing for the following parameters: Tensile modulus was tested using ISO 527. Tensile strength was tested using ISO 527. Tensile elongation (at break) was tested using ISO 527. Flexural modulus was tested using ISO 178. Flexural strength was tested using ISO 178. Notched Charpy impact was tested using ISO 179. Unnotched Charpy impact was tested using ISO 179. Fire retardancy (FR) testing may include testing for the following parameters: Material FR testing is performed using UL 94. Flame testing is performed using ASTM E84-3. Weatherability testing includes testing for the following parameters: Lifecycle UV testing (10, 15, and 20 years) is performed using AATCC Method 16 Option 3. Color fade is determined by measuring the change in color at specified points. Scratch testing is performed using ASTM 50452. Paint adhesion testing is done for the following parameters: Cross hatch test is done using ISO 2409. Humidity and cross hatch test are done together using ISO 6270-2 and ISO 554. Cross hatch test after UV exposure is done as per ISO 2409. Example 1: Samples (dry and wet) at a frequency of 3 GHz [Table 6]
[0100] Table 6 shows the example data for Example 1. Example 2: Samples (dry and wet) at a frequency of 28 GHz [Table 7] [Table 8]
[0101] Tables 7 and 8 show the data from Example 2. Example 3: Samples (dry and wet) at a frequency of 39 GHz [Table 9] [Table 10]
[0102] Tables 9 and 10 show the data from Example 3.
[0103] Examples 4-17 include figures showing the results of testing 1 mm thick panels containing various materials (e.g., polyamide, reinforced polyamide, and polycarbonate) for their transmission loss and reflection under wet and dry conditions. The results showed that panels formed from polyamide materials, including reinforced polyamide materials, exhibited superior transmission loss and reflection properties compared to panels formed from other materials, such as polycarbonate. Surprisingly, given the hydrophilic nature of polyamide, those panels containing polyamide performed well when wet. Example 4: PA66 samples (dry and wet) at a frequency of 28 GHz
[0104] FIG. 3A (dry) and FIG. 3B (wet) are graphical data of transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of sample thickness (mm on the X-axis). Example 5: PA66 samples (dry and wet) at a frequency of 39 GHz
[0105] FIG. 4A (dry) and FIG. 4B (wet) are graphical data of transmission loss (in terms of the scattering parameter S21, which is the ratio of transmitted power to incident power, provided in dB on the Y-axis) and reflection (in dB) as a function of sample thickness (mm on the X-axis). Example 6: PA66-GF Samples (Dry and Wet) at a Frequency of 28 GHz
[0106] FIG. 5A (dry) and FIG. 5B (wet) are graphical data of transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of sample thickness (mm on the X-axis). Example 7: PA66-GF Samples (Dry and Wet) at a Frequency of 39 GHz
[0107] FIG. 6A (dry) and FIG. 6B (wet) are graphical data of transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of sample thickness (mm on the X-axis). Example 8: PA66-PPE Samples (Dry and Wet) at a Frequency of 28 GHz
[0108] FIG. 7A (dry) and FIG. 7B (wet) are graphical data of transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of sample thickness (mm on the X-axis). Example 9: PA66-PPE Samples (Dry and Wet) at a Frequency of 39 GHz
[0109] FIG. 8A (dry) and FIG. 8B (wet) are graphical data of transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of sample thickness (mm on the X-axis). Example 10: PA66-IM-GF30 Samples (Dry and Wet) at a Frequency of 28 GHz
[0110] FIG. 9A (dry) and FIG. 9B (wet) are graphical data of transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of sample thickness (mm on the X-axis). Example 11: PA66-IM-GF30 Samples (Dry and Wet) at a Frequency of 39 GHz
[0111] FIG. 10A (dry) and FIG. 10B (wet) are graphical data of transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of sample thickness (mm on the X-axis). Example 12: PC samples (dry and wet) at a frequency of 28 GHz
[0112] FIG. 11A (dry) and FIG. 11B (wet) are graphical data of transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of sample thickness (mm on the X-axis). Example 13: PC samples (dry and wet) at a frequency of 39 GHz
[0113] FIG. 12A (dry) and FIG. 12B (wet) are graphical data of transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of sample thickness (mm on the X-axis). Example 14: PA66+6I / 6T (70 / 30) Samples (Dry and Wet) at a Frequency of 28 GHz
[0114] FIG. 13A (dry) and FIG. 13B (wet) are graphical data of transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of sample thickness (mm on the X-axis). Example 15: PA66+6I / 6T (70 / 30) Samples (Dry and Wet) at a Frequency of 39 GHz
[0115] FIG. 14A (dry) and FIG. 14B (wet) are graphical data of transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of sample thickness (mm on the X-axis). Example 16: PA6 Samples (Dry and Wet) at a Frequency of 28 GHz
[0116] FIG. 15A (dry) and FIG. 15B (wet) are graphical data of transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of sample thickness (mm on the X-axis). Example 17: PA6 Samples (Dry and Wet) at a Frequency of 39 GHz
[0117] FIG. 16A (dry) and FIG. 16B (wet) are graphical data of transmission loss (S21 in dB on the Y-axis) and reflection (in dB) as a function of sample thickness (mm on the X-axis). Example 18: RF Testing - Insertion Loss vs. Distance at Wave Frequencies of 24 to 40 GHz
[0118] As listed in Table 1, some materials were tested by molding the material into 1 ft x 1 ft flat plaques. These plaques were precision machined to obtain a structural thickness of approximately 2.18 mm. A 0.25 mm thick flame retardant (FR) material and a 0.11 mm thick topcoat of decorative color were applied to each plaque using a roller applicator. The coated plaque surface is somewhat rough due to the roller coat application. The structural thickness of all samples is 2.54 mm.
[0119] A horn antenna setup is used to measure the insertion loss (in dB) in the far field in the 24-40 GHz wave frequency spectrum as a function of plaque surface distance from the antenna.
[0120] 17A and 17B represent cyclone plots showing measured insertion loss (dB) data for one of the tested plaques. FIG. 17A is a cyclone plot of insertion loss in dB (Y-axis) measured over a distance span of 0-100 mm in 0.5 mm increments over a 24-40 GHz wave frequency range (X-axis). Each line shown is a distance increment of 0.5 mm. FIG. 17B plots the measured insertion loss variation (Y-axis) of the tested plaque over a distance variation of 0-100 mm and a frequency range of 24-40 GHz. Example 19: Array antenna testing at 28GHz wave frequency
[0121] The plaque samples described in Example 18 above were then tested using a phased array antenna tuned to 28 GHz.
[0122] The changes in radiation and reflection patterns, e.g., main lobe, side lobe, reflection, boresight error, and relative insertion loss (in dB) were measured at 28 GHz frequency and two radio antenna distances, i) close to each other (see the "0 mm distance" plot in FIG. 18A), and ii) several wavelengths apart (see the "25 mm distance" plot in FIG. 18B). Incident beam measurements for main beam boresight loss, error, 3 dB beamwidth change, first side lobe increase, and back lobe / reflection lobe increase were performed at three azimuth angles, 0°, 30°, and 60°. The term "azimuth angle" is an angular measurement in a spherical coordinate system. In FIG. 18A and FIG. 18B, the solid lines represent the baseline performance of the two antenna systems between the plaque samples, and the dashed lines represent the plaque performance tested with the two antenna systems at 0 mm and 25 mm distance separation.
[0123] In FIG. 18A, for "0 mm distance," the main lobes of each of the azimuth angles show little loss, and the side lobes are improved. Example 20: Enclosure for telecommunications equipment in the frequency range of 500 MHz to 6 GHz
[0124] The three-dimensional enclosure is prepared from panels made of glass fiber reinforced thermoplastic polymer. The thickness of the panel structure is about 2 mm excluding paint coating. The enclosure houses the telecommunications equipment, i.e. radios, antennas, and power supplies. In the radio signal frequency range of 500 MHz to 6 GHz, signal attenuation of 1 dB to 0 dB is observed. Example 21: Enclosure for telecommunications equipment in the frequency range of 24 GHz to 30 GHz
[0125] The three-dimensional enclosure is prepared from panels made of glass fiber reinforced thermoplastic polymer. The thickness of the panel structure is about 3 mm excluding paint coating. The enclosure can house telecommunication devices such as capacitors, actuators, power cable terminations, miniaturized antennas, power converters / power conditioners, optical fibers, radios, diplexers / multiplexers, coaxial cables, and combinations thereof, and can function as, for example, antenna concealment, mobile phone casing, housing for electronic components, fiber termination box, coaxial cable sheath, etc. In the radio signal frequency band of 24 GHz to 30 GHz, signal attenuation of 1 dB to 0 dB is observed. Example 22: Enclosure for telecommunications equipment in the frequency range of 36 GHz to 40 GHz
[0126] The three-dimensional enclosure is prepared from panels made of glass fiber reinforced thermoplastic polymer. The thickness of the panel structure is about 2 mm excluding paint coating. The enclosure can house telecommunication devices such as capacitors, actuators, power cable terminations, miniaturized antennas, power converters / power conditioners, optical fibers, radios, diplexers / multiplexers, coaxial cables, and combinations thereof, and can function as, for example, antenna concealment, mobile phone casing, housing for electronic components, fiber termination box, coaxial fiber sheath, etc. In the radio signal frequency band of 36 GHz to 40 GHz, signal attenuation of 1 dB to 0 dB is observed. Comparative Example 1: Panel with a window for electromagnetic signal transmission
[0127] 20A-20C are schematic diagrams of panels 3A-3C. Panels 3A-3C include respective openings 5A-5C. Panels 3A-3C can have any number of suitable geometric shapes, such as a square shape, a rectangular shape (3A), a cylindrical shape (3B), a disk shape (3C), or any other suitable shape.
[0128] An enclosure (not shown) formed from one or more of such panels can house one or more items of electromagnetic equipment. Examples of electromagnetic equipment include, for example, circuit breakers / three-phase electrical wires terminated to disconnects, power transformers / power conditioners, fiber optic wires and fiber termination boxes, radio(s), diplexers / multiplexers (for radios), coaxial cables from radios to antennas, and / or antennas. The enclosure may also require coaxial feed-throughs to remote antenna mounting locations. The enclosure is designed to accommodate any target application and may have temperature control systems (fans, vents, or slots), doors for internal components (screwed, clipped, hinged), and mounting accessories (brackets, threaded mounting, swivel mounting, sliding guides), etc.
[0129] The openings 5A, 5B, or 5C may be fitted with window structures or assemblies constructed from any suitable material that allows for the transmission of electromagnetic signals. Examples include single or multi-layer transparent films, sheets, glass covers, metal or plastic meshes, etc. There may be multiple such openings of different shapes and sizes to accommodate electromagnetic signal transport with reduced signal strength loss.
[0130] While such panels and housings formed therefrom may be of any suitable material, such as polymers, plastics, foams, metals, composites, etc., the incorporation of openings necessary for signal transmission makes such housings composite to design, manufacture, install, and maintain. Furthermore, such panels and housings made therefrom may have openings or windows attached to a material different from the panel material, resulting in lower durability (e.g., shorter life cycle) while such structures compromise their structural integrity, mechanical strength, and impact resistance. As used in this disclosure, a housing is considered "windowless" if it lacks such openings or windows attached to a material different from the panel material. Example 23: Panel through which electromagnetic signals are transmitted or received
[0131] 21A-21C are schematic diagrams of housings 23, 25, and 27. In comparison with Comparative Example 1, housings 23, 25, and 27 have thicknesses as described in the Examples herein and do not have separate openings or windows for transmission or reception of electromagnetic signals. The housings can be any suitable geometric shape, such as square, rectangular (housing 23 in FIG. 21A), cylindrical (housing 25 in FIG. 21B), disk-shaped (housing 27 in FIG. 21C), dome-shaped, conical, or any suitable shape.
[0132] The formed housing is a portion of a continuously molded article. The article described in this example may be useful for providing weatherproof shielding for electronic equipment. Such a housing (not shown), or an article formed from one or more of such housings, may house one or more items of electromagnetic equipment. The electronic equipment may include, for example, circuit breakers / three-phase electrical wires terminated to no connection, power transformers / power conditioners, fiber optic wires and fiber termination boxes, radio(s), diplexers / multiplexers (for radios), coaxial cables from radios to antennas, and antennas. The housing may also require coaxial feed-throughs to remote antenna mounting locations. The housing is designed to accommodate any target application, with temperature control systems (fans, vents, or slots), doors for internal components (screwed, clipped, hinged), and mounting accessories (brackets, swivel mounts, slider mounts), etc.
[0133] While transmission and reception of electromagnetic signals occurs through the body of the enclosure, the absence of any openings or windows makes such enclosures simple to design, manufacture, install, and maintain. Furthermore, such panels and enclosures made therefrom have a greater durability (e.g., last longer) such that their structural integrity, strength, and impact resistance are well preserved due to the absence of openings or windows that are fitted with a material different from the panel material. Example 24: PA66-based panels and enclosures for transmitting or receiving 30 GHz frequency electromagnetic signals
[0134] Several panel constructions are molded using a PA66-based thermoplastic resin labeled "PA66-IM-GF30," which corresponds to the sample labeled "L" (50% RH) in Table 1 of this disclosure. PA66-IM-GF30 is prepared using INVISTA™ PA66 material and further contains an impact modified polyolefin with 30% by weight glass fiber (GF) reinforcement. The densities of the four panels are 1.097, 1.244, 1.277, and 1.361 g / cc.
[0135] The panels so formed were joined to form a three-dimensional rectangular enclosure having dimensions of 48 inches L x 24 inches W x 12 inches D (or 4 feet L x 2 feet W x 1 foot D). Appropriate network telecommunications equipment was housed within the enclosure. The enclosure did not contain separate openings or windows with any transparent medium such as films, glass coverings, sheets, etc. The PA66-IM-GF30 resin sample had a dielectric constant of 3.5, a dissipation factor (DF) of 0.0142, both measured at a frequency of 30 GHz.
[0136] The structural thickness of the panel wall was maintained at approximately 3 mm for the transmission and reception of 30 GHz frequency electromagnetic signals having less than 0.5 dB loss during their transmission across the panel wall, which electromagnetic signal transmission and reception does not occur through a transparent or optical window. Example 25: PA66-based panels and enclosures through which 40 GHz frequency electromagnetic signals are transmitted or received
[0137] Several panel constructions were molded using a PA66 based thermoplastic labeled "PA66-PPE" which corresponds to the sample labeled "H" (50% RH) in Table 1 of this disclosure. PA66-PPE is an unreinforced thermoplastic. The density of the panels is ≧1.1 g / cc and ≦1.4 g / cc.
[0138] The panels so formed were joined to form a three-dimensional cylindrical enclosure having dimensions of about 22 feet to about 36 inches outside diameter and about 0.5 feet to about 6.5 feet long (or a 3 foot outside diameter by 5 foot long cylinder). Appropriate network telecommunications equipment was housed within the enclosure. The enclosure did not contain any separate openings or windows having any transparent medium such as films, glass coverings, sheets, etc. The PA66-PPE resin sample had a relative dielectric constant of about 2.82, a dissipation factor (DF) of about 0.0074, both measured at a frequency of 40 GHz.
[0139] The structural thickness of the panel wall was maintained at approximately 4 mm for the transmission and reception of 40 GHz frequency electromagnetic signals having less than 0.5 dB loss during their transmission across the panel wall, which did not occur through a transparent or optical window. Example 26: PA66-based panels and enclosures through which sub-6 GHz (3 GHz) frequency electromagnetic signals are transmitted or received
[0140] Several panel constructions were molded using a PA66 based thermoplastic labeled "PA66-PPE" which corresponds to the sample labeled "H" (about 50% RH) in Table 1 of this disclosure. PA66-PPE is an unreinforced thermoplastic. The density of the panels is ≧1.1 g / cc and ≦1.4 g / cc.
[0141] The formed panels are joined to form a three-dimensional clamshell shaped enclosure intended for sub-6 GHz 5G and 4G LTE wireless device shrouding. Suitable network telecommunication equipment is housed within the enclosure. The enclosure does not include a separate opening or window with any transparent medium such as a film, glass covering, sheet, etc. The PA66-PPE resin sample has a dielectric constant of about 2.84, a dissipation factor (DF) of about 0.0095, both measured at a frequency of 3 GHz.
[0142] The structural thickness of the panel wall was maintained at approximately 4 mm for the transmission and reception of 3 GHz frequency electromagnetic signals having less than 0.5 dB loss during their transmission across the panel wall, which electromagnetic signal transmission and reception does not occur through a transparent or optical window.
[0143] This polyamide-based clamshell radio shroud weighs approximately 20-25 lbs and provides a cost-effective and durable solution for the sub-6 GHz 5G and 4G LTE radio frequency transmission markets. A comparable metal shroud with the necessary openings for radio transmission and reception functions would be more expensive, less durable, and heavier (approximately 60-70 lbs). Example 27: RF Testing - Insertion Loss vs. Distance at RF Frequencies from 24 to 40 GHz
[0144] Similar to Example 18, a horn antenna setup was used to measure insertion loss (S21 in dB) in the far field of the 24-40 GHz wave frequency spectrum as a function of test sample plaque surface distance from the antenna. As listed in Table 1, several materials were tested by molding the material into 1 foot by 1 foot flat plaques. These plaques were precision machined to obtain a structural thickness of approximately 2.18 mm. A 0.56 mm thick flame-retardant (FR) material and a 0.15 mm thick topcoat of decorative color were applied to each plaque using a spray coating technique. The structural thickness of all samples is 2.89 mm.
[0145] Figure 22 is a cyclone plot of insertion loss in dB (Y-axis) measured over a distance span of 0 to 100 mm in 0.5 mm increments over a frequency range of 24 to 40 GHz (X-axis). Each line shown is a distance increment of 0.5 mm. Example 28: Array antenna testing at 28GHz wave frequency
[0146] The plaque samples described in Example 24 above were then tested using a phased array antenna tuned to 28 GHz.
[0147] The changes in radiation and reflection patterns, e.g., main lobe, side lobe, reflection, boresight error, and relative insertion loss (in dB) were measured for a 28 GHz frequency and two radio antenna distances: i) close to each other (plot "0 mm distance" in FIG. 23A); ii) several wavelengths apart (plot "25 mm distance" in FIG. 23B). Incident beam measurements for main beam boresight loss, error, 3 dB beamwidth change, first side lobe increase, and back lobe / reflection lobe increase were measured at three azimuth angles: 0°, 30°, and 60°. ° It was carried out.
[0148] In Figures 23A-B, the solid lines represent the baseline performance of the two antenna system between plaque samples, and the dashed lines represent plaque performance tested with the two antenna system at 0 mm and 25 mm separation distances.
[0149] In Figures 23A-23B, for "0 mm distance" and "25 mm distance", respectively, the main lobe at each azimuth angle shows little loss and the side lobes are improved compared to those in Figures 18A-18B of Example 19. Example 29: Mechanical Performance Data for Samples in Table 1
[0150] Several of the material samples from Table 1 were tested for mechanical performance. Specifically, samples of material labeled "G" [DAM] and "H" [Cond] for PA66+PPE, and materials labeled "C" [DAM] and "D" [Cond] for PA66+GF30 were tested. Additional samples were prepared using 20 wt% GF reinforced PA66+PPE and 20 wt% GF reinforced PA66 materials (not shown in Table 1) and are referred to as "PA66+PPE GF20" and "PA66 GF20", respectively. Tables 11A-F below provide mechanical performance data for samples tested at three temperatures, -40°C, 23°C, and 50°C.
[0151] [Table 11]
[0152] [Table 12] [Table 13] [Table 14] [Table 15] [Table 16] Example 30
[0153] This Example 30 shows a range of thicknesses for nylon 6,6 with no glass reinforcing fiber (Example 30a), and nylon 6,6 containing 30 weight percent glass reinforcing fiber (Example 30b) and polycarbonate (Example 30c). [Table 17] [Table 18] [Table 19] Examples 31A-E: Samples containing PA66 / DI blends
[0154] Several formulations are prepared containing PA66 / DI with glass fiber, FR additives, heat stabilizer additives, and UV stabilizers within the composition ranges shown in Table 13. [Table 20]
[0155] In the formulations of Table 13, non-limiting examples of FR additives can include Exolit® OP 1080P, Exolit® OP 1314, Exolit® OP 1400, etc. Exolit® FR additives are commercially available from Clariant.
[0156] In the formulations of Table 13, non-limiting examples of UV stabilizer additives can include Carbon Black (19 nm range), organic UV / heat stabilizers such as Irganox® commercial products, phosphite-based commercial additives, hindered amine light (HAL) stabilizers (e.g., Nylostab® products), UV absorber additives, and combinations thereof.
[0157] In the formulations of Table 13, non-limiting examples of heat stabilizers and chain extender additives can include copper or organic based, such as Irganox® B1171, Irganox® B1098, Bruggolen™ TP-H1802, Bruggolen™ M1251, etc. For example, Irganox® B1171 is a commercial polymer additive product from BASF.
[0158] Colorant additives may be added during the molding process for the formulations in Table 13. Non-limiting examples of such colorant additives include commercial products available in the thermoplastic industry.
[0159] Test plaques are prepared using the formulations in Table 13 and as described above in the "Determination of Dielectric Constant and Loss Tangent" section. The dielectric constant and loss tangent values are determined by the test method described above and a signal frequency range of 20-40 GHz. Table 14 provides a summary of the dielectric performance data measured for various samples prepared according to the present disclosure. The term "loss tangent" is a measure of how much a wave is attenuated by absorption through a medium. [Table 21] Example 32A-C: FR performance test for PA66 samples
[0160] In Table 15 below, flame retardant [FR] performance data is summarized for several samples according to the present disclosure. The samples tested achieved an overall UL-94 test rating of V-0. A similar UL-94 test rating of V-0 is expected for PA66 / DI samples with 20 wt% GF reinforcement, 20 wt% FR additive, and up to 3 wt% each of UV additive and colorant. The FR coatings used in Table 15 are commercially available. [Table 22]
[0161] There are a variety of tests and standards that can be used to evaluate the flame retardancy of a polymer resin system. Underwriters' Laboratories test number UL 94 serves as one industry standard test for flame-retardant thermoplastic compounds. The "UL 94 Standard for Testing for Flammability of Plastic Materials for Devices and Appliance Parts" provides details of the test methods and criteria for evaluation. Test method ASTM D635 is the standard test method for the burn rate or burn area and burn time of plastics in a horizontal position. Test method ASTM D3801 is the standard test method for measuring the comparative burn characteristics of solid plastics in a vertical position. Vertical burn test ratings (e.g., V-0, V-1, V-2) are more severe and difficult to achieve than the horizontal burn ratings (HB-1, HB-2, HB-3).
[0162] Surprisingly, the examples showed that a nylon 6,6-based formula could be developed to meet the mechanical requirements of the mmWave housing while transmitting sufficient mmWave signals to be useful in 5G services. One of the reasons for this is surprising: nylon 66 absorbs water, which is believed to have a negative effect on transmission. Another unexpected beneficial property of the formulation found is its better compatibility with various additives than other base thermoplastic materials such as polypropylene and polycarbonate. Thermoplastics were found to be beneficial for their excellent processability. Surprisingly, it was also found that the addition of 5, 10, 20, 30, or more weight percent glass fibers (to improve tensile strength and toughness) resulted in compounded polyamides with acceptable mmWave transmission properties.
[0163] As shown in Example 30a for nylon 6,6 with no added glass fibers, the attenuation coefficient values can be in the range of up to 3.9 dB / GHz.cm (at 0.5 GHz wave frequency) or in the range of 0.05-0.07 dB / GHz.cm (at 81 GHz wave frequency). Example 30b for nylon 6,6 with 30 wt. % glass fibers, the attenuation coefficient values can be in the range of up to 5.25 dB / GHz.cm (at 0.5 GHz wave frequency), or in the range of 0.10-0.20 dB / GHz.cm (at 36 GHz wave frequency), or in the range of 0.055-0.075 dB / GHz.cm (at 81 GHz wave frequency). Similarly, in Example 30c for polycarbonate without added glass fibers, the attenuation coefficient values can range up to 3.0 dB / GHz.cm (at 0.5 GHz wave frequency) or can range from 0.03 to 0.045 dB / GHz.cm (at 81 GHz wave frequency).
[0164] The terms and expressions that have been used are used as terms of description, not of limitation, and there is no intention in the use of such terms and expressions to exclude any equivalents of the features shown and described or portions thereof, but it is recognized that various modifications are possible within the scope of the aspects of the invention. Thus, while the invention has been specifically disclosed by certain aspects and optional features, it will be understood that modifications and variations of the concepts disclosed herein may be reclassified by those skilled in the art, and that such modifications and variations are considered to be within the scope of the invention as defined by the scope of the aspects of the invention. Enumeration of aspects.
[0165] The following aspects are provided, but the numbering should not be construed as designating an order of importance.
[0166] A first aspect is a housing article for protecting a wireless antenna operating in a frequency range of 0.5 GHz to 81 GHz, the housing article being made of a thermoplastic resin, A first polyamide, Nylon-6, Nylon-6,6, Nylon-6 or a copolymer of nylon-6,6, Poly(hexamethylene terephthalamide), Poly(hexamethylene isophthalamide), or a copolymer comprising at least one repeat unit which is a copolymer of poly(hexamethylene terephthalamide) and poly(hexamethylene isophthalamide); a mixture thereof, or a first polyamide, including copolymers thereof; A housing article is provided that includes a thermoplastic resin that includes a second polyamide, an additive, or a mixture thereof.
[0167] Example 2 provides the housing article of Example 1, comprising a first plate of a first thickness and a second plate of a second thickness.
[0168] Example 3 provides the housing article of example 2, wherein the first plate and the second plate separately attenuate electromagnetic signals.
[0169] In a fourth aspect, the thermoplastic resin is A first polyamide; a second polyamide; and an additive.
[0170] Aspect 5 is a method for preparing a polyamide comprising the steps of: Nylon-6 or nylon-6,6, A copolymer comprising nylon-6 or nylon-6,6, the copolymer comprising: Poly(hexamethylene terephthalamide), Poly(hexamethylene isophthalamide), a copolymer of poly(hexamethylene terephthalamide) and poly(hexamethylene isophthalamide), the molar ratio of poly(hexamethylene terephthalamide) repeat units to poly(hexamethylene isophthalamide) repeat units being in the range of about 60:40 to about 90:10; or and a copolymer comprising at least one repeat unit that is a mixture thereof.
[0171] A sixth aspect is directed to a method for preparing a polyamide comprising the steps of: Nylon-6 or nylon-6,6, Nylon-6 or nylon-6,6, Poly(hexamethylene terephthalamide), Poly(hexamethylene isophthalamide), and / or and at least one repeat unit that is a copolymer of poly(hexamethylene terephthalamide) and poly(hexamethylene isophthalamide), wherein the molar ratio of poly(hexamethylene terephthalamide) repeat units to poly(hexamethylene isophthalamide) repeat units is in the range of about 70:30 to about 75:25.
[0172] Example 7 provides the housing article of any one of Examples 1-6, wherein the first polyamide is at least one of nylon-6 and nylon-6,6.
[0173] Example 8 provides the housing article of any one of Examples 1-7, wherein the thermoplastic resin includes an additive, the additive being a reinforcing fiber at a level of up to 50% by weight of the thermoplastic resin.
[0174] Example 9 provides the housing article of example 8, wherein the reinforcing fibers comprise glass fibers, silicon fibers, carbon fibers, polypropylene fibers, polyacrylonitrile fibers, basalt fibers, or a mixture thereof.
[0175] Example 10 provides the housing article of any one of Examples 8 or 9, wherein the reinforcing fibers comprise glass fibers.
[0176] Example 11 provides the housing article of any one of Examples 1-10, wherein the thermoplastic resin comprises an additive, and the additive is selected from a UV resistance additive, a flame retardant additive, an antistatic additive, an impact modifier, a colorant, a water repellent, or a combination thereof.
[0177] Example 12 provides the housing article of any one of Examples 1 to 11, wherein the thermoplastic resin includes an additive, and the additive is in a range of about 0.1% to about 30% by weight of the thermoplastic resin.
[0178] Aspect 13 provides a housing article according to any one of Aspects 1 to 12, wherein the thermoplastic resin includes an additive, the additive being in a range of about 10% by weight to about 30% by weight of the resin, and the thermoplastic resin has a transmission loss of less than 2 decibels (dB) for signals having frequencies between 500 MHz and 40 GHz.
[0179] A fourteenth aspect provides a housing article according to any one of the first to thirteenth aspects, wherein the transmission loss of the thermoplastic resin within at least one of a frequency range of 0.5 GHz to 6 GHz, a frequency range of 24 GHz to 30 GHz, and a range of 36 GHz to 40 GHz is less than 1 decibel (dB).
[0180] Example 15 provides the housing article of example 14, wherein the thermoplastic resin has a transmission loss of less than 0.5 decibels (dB).
[0181] Example 16 provides the housing article of any one of Examples 1-15, wherein the article completely encloses the wireless antenna.
[0182] Example 17 provides a housing article of any one of Examples 1-15, wherein the article comprises a panel.
[0183] Example 18 provides the housing article of example 17, wherein the article has a uniform thickness.
[0184] Example 19 provides the housing article of any one of Examples 17 or 18, wherein the article has a convex profile, a concave profile, or a wavy profile.
[0185] Example 20 provides the housing article of any one of Examples 17-19, wherein the panel is windowless.
[0186] Aspect 21 provides a housing article according to any one of aspects 1-20, wherein the article is weather resistant.
[0187] Example 22 provides the housing article of any one of Examples 1 to 21, wherein the article has a relative weight gain due to moisture uptake of less than 4% upon equilibration in an atmosphere at 70° C. and 62% relative humidity.
[0188] A twenty-third aspect is directed to a thermoplastic resin comprising a reinforcing glass fiber at a level of up to 50 weight percent of the total composition mass, the thermoplastic resin comprising: A tensile strength in the range of about 40 MPa to about 300 MPa; 0.7g / cm 3 ~5g / cm 3 With a density in the range of 40kJ / m 2 ~150kJ / m 2 With impact resistance in the range of When the direction of the signal impinging on the article is perpendicular to the surface of the article, the article thickness is substantially uniform over the area where the signal impinges on the article, hereinafter: When the thickness of the article is 0.5mm to 6mm, the signal loss is 1dB to 0dB for a frequency of 500MHz to 6GHz. When the thickness of the article is 0.5mm to 4.5mm, the signal loss is 1dB to 0dB for a frequency of 24GHz to 30GHz. When the article thickness is 0.5 mm to 4 mm, the signal loss is 1 dB to 0 dB for signals with frequencies of 36 GHz to 40 GHz, and The housing article according to any one of aspects 1 to 22 has at least one signal attenuation of 1 dB to 0 dB for a signal having a frequency of 76 GHz to 81 GHz when the article thickness is 0.5 mm to 3.5 mm.
[0189] A twenty-fourth aspect of the present invention relates to an article having a density of: 0.7g / cm 3 More than ~5g / cm 3 below, 0.8g / cm 3 More than ~4g / cm 3 The following, and 0.85 or more~3g / cm 3 The housing article of any one of aspects 1-23 is provided, in a range selected from the following:
[0190] Example 25 provides the housing article of any one of Examples 1 to 24, wherein the thermoplastic resin comprises 10 to 50 weight percent glass fibers.
[0191] Example 26 provides the housing article of example 25, wherein the thermoplastic resin comprises 12 to 50 weight percent glass fiber.
[0192] Example 27 provides the housing article of Example 26, wherein the thermoplastic resin comprises 14 to 40 weight percent glass fiber.
[0193] Example 28 provides the housing article of any one of Examples 25 to 27, wherein the thermoplastic resin has a tensile strength in the range of 40 to 300 MPa.
[0194] Aspect 29 is When the article thickness is 1.5mm~4mm, for signals with frequencies of 500MHz~6GHz, 1B~0dB; dB~0 dB for signals with frequencies from 24 GHz to 30 GHz when the article thickness is 2.5 mm~4 mm; 1B to 0 dB for signals with frequencies between 36 GHz and 40 GHz when the article thickness is between 1.75 mm and 2.75 mm; or A housing article according to any one of aspects 1 to 28 is provided, having a substantially uniform signal attenuation of 1 dB to 0 dB for signals with frequencies between 76 GHz and 81 GHz when the article thickness is between 1.75 mm and 2.75 mm.
[0195] Example 30 provides the housing article of any one of Examples 1-29, comprising at least one of up to 20% of a flame retardant additive or a flame retardant coating, and wherein the housing article has a UL-94 test rating of V-0.
[0196] Example 31 provides the housing article of any one of Examples 1 to 30, wherein the thermoplastic resin comprises PA66:DI (85:15 to 96:4 wt:wt), glass fiber in the range of about 5 to about 20 wt %, flame retardant additive in the range up to about 20 wt %, UV additive in the range up to about 3 wt %, heat stabilizer additive in the range up to about 2 wt %, and colorant additive in the range up to about 3 wt %.
[0197] Example 32 provides the housing article of any of Examples 1-31, wherein the housing article is formed by one of injection molding, thermoforming, compression molding, or extrusion.
[0198] Example 33 provides a system comprising the housing article of any one of Examples 1 to 32 spaced apart from a radio antenna.
[0199] Example 34 provides the system of example 33, wherein the wireless antenna operates in a frequency band associated with 5G broadband cellular network technology.
[0200] Aspect 35 is a system, comprising: A radio antenna; A housing article according to any one of aspects 1-34, substantially enclosing a radio antenna.
[0201] Example 36 provides the system of example 35, wherein the wireless antenna operates in a frequency band associated with 5G broadband cellular network technology.
[0202] Example 37 provides a housing article for protecting a radio antenna operating in a frequency range of 0.5 GHz to 81 GHz, the housing article comprising nylon-6,6.
[0203] Example 38 provides a method that includes transmitting electromagnetic radiation through the housing of any one of examples 1-37.
Claims
1. A housing article for protecting a wireless antenna operating in the frequency range of 0.5 GHz to 81 GHz, the housing article comprising a thermoplastic resin composition comprising the following (A) to (F): (A) 85:15 to 96:4 wt:wt PA66 / DI, wherein the DI comprises a combination of 2-methyl-pentamethylene diamine and isophthalic acid; (B) reinforcing fibers in the range of 5 to 20% by weight; (C) a flame retardant additive in the range of up to 20% by weight; (D) a UV additive in the range of up to 3% by weight; (E) a heat stabilizer additive in the range of up to 2% by weight, and (F) Colorant additive in the range of up to 3% by weight
2. 10. The housing article of claim 1, wherein the reinforcing fibers comprise glass fibers, silicon fibers, carbon fibers, polypropylene fibers, polyacrylonitrile fibers, basalt fibers, or mixtures thereof.
3. The housing article of claim 1 or 2, wherein the reinforcing fibers comprise glass fibers.
4. The housing article according to any one of claims 1 to 3, wherein the thermoplastic resin composition has a transmission loss of less than 2 decibels (dB) for signals having a frequency of 500 MHz to 40 GHz.
5. The transmission loss of the thermoplastic resin composition within at least one of the frequency ranges of 0.5 GHz to 6 GHz, 24 GHz to 30 GHz, and 36 GHz to 40 GHz is less than 1 decibel (dB). The housing article according to any one of claims 1 to 4.
6. 6. The housing article of claim 5, wherein the transmission loss of the thermoplastic resin composition is less than 0.5 decibels (dB).
7. The housing article of any one of claims 1 to 6, wherein the article completely encloses the radio antenna.
8. The housing article of any one of claims 1 to 6, wherein the article comprises a panel.
9. The housing article of claim 8 , wherein the article has a uniform thickness.
10. 10. The housing article of claim 8 or 9, wherein the article has a convex profile, a concave profile, or a wavy profile.
11. The housing article of any one of claims 8 to 10, wherein the panel is windowless.
12. The housing article of any one of claims 1 to 11, wherein the article is weather resistant.
13. 13. The housing article of any one of claims 1 to 12, wherein the relative weight gain of the article due to moisture uptake is less than 4% when equilibrated in an atmosphere at 70°C and 62% relative humidity.
14. The thermoplastic resin composition comprises reinforcing glass fibers at a level of up to 20 weight percent of the total composition mass, the thermoplastic resin composition comprising: A tensile strength in the range of 40 MPa to 300 MPa, measured according to the method of ISO 527 at 23 to 50 ° C.; A density in the range of 0.7 g / cm3 to 5 g / cm3; 40 kJ / m, measured according to ISO 179 2 ~150kJ / m 2 With unnotched Charpy impact resistance in the range of If the direction of the signal impinging on the article is perpendicular to the surface of the article, the article thickness is uniform over the area where the signal impinges on the article, hereinafter: When the article thickness is 0.5 mm to 6 mm, 1 dB to 0 dB for signals having frequencies of 500 MHz to 6 GHz; When the article thickness is 0.5 mm to 4.5 mm, the noise level is 1 dB to 0 dB for signals having a frequency of 24 GHz to 30 GHz; When the article thickness is between 0.5 mm and 4 mm, for signals having frequencies between 36 GHz and 40 GHz, between 1 dB and 0 dB; and The housing article of any one of claims 1 to 13, having at least one signal attenuation of 1 dB to 0 dB for signals having a frequency of 76 GHz to 81 GHz when the article thickness is 0.5 mm to 3.5 mm.
15. The density of the article is 0.7g / cm3 or more to 5g / cm3 or less, 0.8g / cm3 or more to 4g / cm3 or less, and The housing article according to any one of claims 1 to 14, wherein the density is in a range selected from 0.85 or more and 3 g / cm3 or less.
16. When the article thickness is 1.5 mm to 4 mm, the signal frequency is 500 MHz to 6 GHz, and the signal frequency is 1 dB to 0 dB. When the article thickness is 2.5 mm to 4 mm, the noise level is 1 dB to 0 dB for signals having a frequency of 24 GHz to 30 GHz; 1 dB to 0 dB for signals having a frequency between 36 GHz and 40 GHz when the article thickness is between 1.75 mm and 2.75 mm; or The housing article of any one of claims 1 to 15, having a uniform signal attenuation of 1 dB to 0 dB for signals with frequencies between 76 GHz and 81 GHz when the article thickness is between 1.75 mm and 2.75 mm.
17. 17. The housing article of any one of claims 1 to 16, comprising up to 20% at least one of a flame retardant additive or a flame retardant coating, the housing article having a UL-94 test rating of V-0.
18. The housing article of any of claims 1-17, wherein the housing article is formed by one of injection molding, thermoforming, compression molding, or extrusion.
19. A system comprising the housing article of any one of claims 1 to 18, spaced apart from the radio antenna.
20. 20. The system of claim 19, wherein the wireless antenna operates in a frequency band associated with 5G broadband cellular network technology.
21. 1. A system comprising: The radio antenna; A system comprising: the housing article according to any one of claims 1 to 18, surrounding the radio antenna.
22. 22. The system of claim 21, wherein the wireless antenna operates in a frequency band associated with 5G broadband cellular network technology.
23. The housing article of any one of claims 1 to 18 for protecting a radio antenna operating in the frequency range of 3 GHz to 40 GHz.
24. A method comprising transmitting electromagnetic radiation through an enclosure according to any preceding claim.
Citation Information
Patent Citations
Filling polyamide molding material showing reduction of water-absorbing property
JP2008189929A
Reinforced polyamide composition and article having low shrinkage and excellent surface appearance
JP2012513499A
Conductive polyamide substrate
JP2015520800A
Polyamide molding composition and multilayer structure molded from the same
JP2018095838A
Polyamide composition and molded article
JP2018188534A